MENGEMBANGKAN LITERASI HUMANISTIK SISWA SEKOLAH DASAR MELALUI PEMBELAJARAN IPA - Septiari Dewi, Putu Ayu; Budi Wijaya, I Komang Wisnu (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
The 21st century is characterized as the information age where information is a necessity. The rapid flow of information requires good literacy skills to manage circulating information. One of the literacy needed is humanistic literacy. This study aims to describe and analyze ways to develop humanistic literacy of elementary school students through learning science. This research is a literature study. Data sources are in the form of books, journals, papers and other sources related to humanistic literacy and science learning. The data were analyzed by content analysis techniques. The results of the study state that humanistic literacy can be developed in elementary school students through science learning by developing group learning, student-centered learning and making creative and selling products. The teacher's role in developing humanistic literacy is as a learning developer, facilitator, motivator and evaluator.